Japanese encephalitis in Bali, Indonesia: ecological and socio-cultural perspectives. Issue 1 (1st January 2021) - Kardena, I Made; Adi, Anak Agung Ayu Mirah; Astawa, Nyoman Mantik; O'Dea, Mark; Laurence, Michael; Sahibzada, Shafi; Bruce, Mieghan
ABSTRACT: The increasing number of cases of acute encephalitis syndrome, a key presenting clinical sign of Japanese encephalitis infection in humans, along with increasing laboratory confirmed cases in Bali over recent years have led to the Indonesian government developing a national program of vaccination against Japanese encephalitis virus. In order to inform multidisciplinary management, a review was conducted to assess Japanese encephalitis virus-related cases in humans and animals including their determinants and detection in vectors. Along with published literature, key data from local authorized officers in Bali have been used to convey the recent situation of the disease. Related surveys detected up to 92% of the local children had antibodies against the virus with the annual incidence estimated to be 7.1 per 100, 000 children. Additionally, reports on young and adult cases of infection within international travellers infected in Bali were documented with both non-fatal and fatal outcomes. Further seroprevalence surveys detected up to 90% with antibodies to the virus in animal reservoirs. The detection of the virus in certain Culex mosquito species and high levels of seropositivity may be associated with greater risk of the virus transmission to the human population. It was also highlighted that local sociocultural practices for agriculture and livestock were potentially associated with the high density of the vector and the reservoirs, which then may lead to the risk of the disease transmission in the ecology of Bali.